2020
DOI: 10.1111/1750-3841.15101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high hydrostatic pressure challenge on biogenic amines, microbiota, and sensory profile in traditional poultry‐ and pork‐based semidried fermented sausage

Abstract: The processing of traditional poultry-and pork-based semidried fermented smoked sausages needs to be modernized to improve product quality and further extend its shelf life. The aim of the present study was to apply different combinations of high pressure (300 to 600 MPa) and time (154 to 1,800 s) on the sausages using an experimental design based on response surface methodology. The chemical, microbial, and sensory characteristics of sausages treated with high-pressure processing (HPP) were investigated. HPP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Use of high hydrostatic pressure (HHP) results in microorganism inactivation, and a change of microorganism structure, genome, and morphology, without impacting the product quality, thus prolonging the shelf-life of the product.The effect of HHP depends largely on the pressure level, treatment time, time of application, and type of food. The analysis of restricting the BA level in sausage based on poultry meat (Alheira) subject to high hydrostatic pressure has shown that the pressure of 600 MPa for 960 s results in limited levels of BA in poultry products without impacting the sensory properties of the product [ 54 ].…”
Section: Methods For Restricting Biogenic Amines Content In Poultry Meatmentioning
confidence: 99%
“…Use of high hydrostatic pressure (HHP) results in microorganism inactivation, and a change of microorganism structure, genome, and morphology, without impacting the product quality, thus prolonging the shelf-life of the product.The effect of HHP depends largely on the pressure level, treatment time, time of application, and type of food. The analysis of restricting the BA level in sausage based on poultry meat (Alheira) subject to high hydrostatic pressure has shown that the pressure of 600 MPa for 960 s results in limited levels of BA in poultry products without impacting the sensory properties of the product [ 54 ].…”
Section: Methods For Restricting Biogenic Amines Content In Poultry Meatmentioning
confidence: 99%
“…Previous research on the physicochemical properties of alheira emphasizes the significant variability in chemical, physical, and sensory attributes from industrial and small-scale producers across localities [39][40][41]. Correlations of the physicochemical and microbiological analysis of a total of 58 alheira sausages are compiled in Figure 3a, and a subset of 22 selected samples from which LAB with high antimicrobial activity were isolated (Section 2.4) are shown in Figure 3b.…”
Section: Alheira Physicochemical and Microbiological Analysismentioning
confidence: 99%
“…In any case, results should be analyzed with care (including fail-safe approach), considering all the constraints and assumptions introduced in simulating the natural contamination present in foods and the accurate reproduction of conditions of foods during storage, distribution, sale, and preparation. Challenge testing is a technique commonly employed in research [ 62 , 184 , 185 , 186 , 187 , 188 ]. Up to a 40% NaCl reduction was achieved during a challenge test in a pre-packed cooked meat product when it was replaced with a commercial mixture of potassium lactate and sodium diacetate without statistically affecting the shelf-life [ 166 ].…”
Section: Use Of Challenge Testing and Shelf-life Testsmentioning
confidence: 99%